Long chain branched impact copolymer of polypropylene: microstructure and rheology - Chikhalikar, Kalyani; Deshpande, Anushree; Pol, Harshawardhan; Dhoble, Deepa Arun; Jha, Saroj; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Kulkarni, Surendra; Gupta, Surendra; Lele, Ashish K. (Polymer Engineering and Science, 2015)
A biphasic impact copolymer of polypropylene (ICP) was modified with peroxide by reactive extrusion process resulting in reduced melt flow index, improved melt strength, and higher die swell. The polymers were for the first time subjected to systematic rheological and microstructural characterization in an effort to understand their structure-property relations. In shear rheological tests, the modified ICP displayed higher flow activation energy, reduced values of loss tangent and nearly equal frequency dependence of storage and loss modulli. The modified ICP also showed strain hardening behaviour in uniaxial extensional rheology and higher crystallization temperature in differential scanning calorimetry (DSC). All these are definitive indications of the presence of long chain branches (LCB). Fitting the rheological data of modified ICPs with the eXtended Pom Pom (XPP) model indicated the presence of LCB on the higher molecular weight fraction in the polymer, a result which was corroborated with multi-detector high temperature gel permeation chromatography (HT-GPC). More importantly, the matrix and rubber phases of the ICP were separately characterized for presence of long chain branching by rheology, DSC and HT-GPC. The results indicate that while LCB existed in the matrix phase, microgels were present in both phases indicating that the reaction with peroxide occurred in both phases. POLYM. ENG. SCI., 55:1463-1474, 2015. (c) 2014 Society of Plastics Engineers

Linear poly(lactic acid) ionomers with pendant ionic groups - Joseph, Seena; Menon, Abhijith Hari; Lele, Ashish K.; Chikkali, Samir H. (New Journal of Chemistry, 2024)
Although PLA is widely used, melt processing of this polymer is still a challenging task. In our efforts to improve the melt strength and processability of PLA, we report the synthesis of high molecular weight linear PLA ionomers. PLA copolymers (CP1-CP3) with pendant alkyne groups were synthesized by reacting L-lactide with propargylated lactide. The existence of copolymers with alkyne groups was unambiguously demonstrated, and the percentage of alkyne was found to be 3-7%. A click reaction protocol was developed to treat the resultant alkyne functionalized copolymers (CP1-CP3) with mercaptosuccinic acid (MSA) and pendant carboxylic acid group functionalized copolymers (CP1-MSA1 to CP3-MSA3) were obtained. The 1-2D NMR confirmed the formation of a major MSA bis-addition product, along with a minor mono-addition product. In the final step, the MSA functionalized copolymers were treated with sodium hydride (NaH) to obtain the corresponding linear PLA ionomers (CP1-MSA1-Na1 to CP3-MSA3-Na3). Significant improvement in thermal and melt rheological properties was observed in these ionomers, as compared to the precursor copolymer and unmodified PLA, due to the microstructural changes caused by the association of the ionic groups. Storage modulus (G `) and loss modulus (G `') values showed a substantial increase in melt elasticity of the ionomers with G ` > G `', whereas the unmodified PLA melt behaved like a viscoelastic liquid. Detailed investigation reveals that incorporating pendant ionic groups in a high molecular weight linear PLA remarkably enhances the elastic modulus from 10 to 100 000 Pa (four orders of magnitude).